Smart/stimuli-responsive hydrogels: State-of-the-art platforms for bone tissue engineering. (December 2022) - El-Husseiny, Hussein M.; Mady, Eman A.; El-Dakroury, Walaa A.; Zewail, Moataz B.; Noshy, Mina; Abdelfatah, Amr M.; Doghish, Ahmed S.
Highlights: The fundamentals of bone biology and the existing strategies for BTE were summarized. Diverse kinds of smart/stimuli-responsive hydrogels used for BTE were outlined. Various techniques to fabricate smart/stimuli-responsive hydrogels were elaborated. The employment of smart/stimuli-responsive hydrogels in BTE was discussed. Existing challenges and future outlook for their use in bone reconstruction were highlighted. Abstract: Repair of bone defects is a time-consuming, self-healing process based on tissue modeling and remodeling. However, the capacity of this method is limited, especially for critical-sized bone defects where bone augmentation is necessary. Hence, bone tissue engineering (BTE) with the execution of curative strategies that merge biomolecules, biomimetic scaffolds, and cells plays a decisive role in this track. Smart/stimuli-responsive hydrogels (SSRHs) are superb three-dimensional (3D) biomaterials intended for tissue engineering and other biomedical implementations. They can imitate the diverse mechanical, biological and physicochemical nature of the natural tissues. Besides, they provide 3D configuration, afford ample aqueous circumstances, and support mechanical constancy necessary for cell growth. Furthermore, they function as competent delivery platforms for various biomolecules. Different nature-derived and synthetic polymers were largely exploited to produce smart scaffolds with distinctive characters and customized functionalities matching BTE applications. In the current review, we outlined the fundamentals of bone biology and the existing strategies for BTE. Moreover, we discussed different SSRHs, their synthesis scheme, their present situation, and future perspectives for BTE. In conclusion, recent progress in the assembly of SSRHs reinforces their potential to serve as smart and intricate platforms for regenerating injured bone tissues. Graphical abstract: Image, graphical abstract